Pengaruh Lingkungan Sekolah dan Disiplin Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak di MA Muhammadiyah Pubian Lampung Tengah - Fajar Abrori (Advances In Education Journal, 2025)
This study aims to analyze the influence of the school environment and learning discipline on students’ learning outcomes in the subject of Akidah Akhlak at MA Muhammadiyah Pubian, Central Lampung. This research employed a quantitative approach using an ex post facto design. The population consisted of all eleventh-grade students, with samples selected through probability sampling techniques. Data were collected through questionnaires, documentation, and observation. Data analysis was conducted using simple and multiple linear regression tests, along with t-test and F-test. The results indicate that: (1) the school environment has a positive and significant effect on students’ learning outcomes; (2) learning discipline has a positive and significant effect on students’ learning outcomes; and (3) both school environment and learning discipline simultaneously have a positive and significant effect on learning outcomes. These findings emphasize the importance of a supportive school environment and strong learning discipline in improving students’ achievement in Akidah Akhlak